Volume 7: Turbomachinery, Parts A, B, and C 2011
DOI: 10.1115/gt2011-46468
|View full text |Cite
|
Sign up to set email alerts
|

Active Flow Control Concepts on a Highly Loaded Subsonic Compressor Cascade: Re´sume´ of Experimental and Numerical Results

Abstract: The paper presents experimental and numerical results for a highly loaded, low speed, linear compressor cascade with active flow control. Three active flow control concepts by means of steady jets, pulsed jets, and zero mass flow jets (synthetic jets) are investigated at two different forcing locations, i.e. at the end walls and the blade suction side. Investigations are performed at the design incidence for jet-to-inlet velocity ratios from approximately 0.7 to 3.0 and two different Reynolds numbers. Detailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In the current study, a Rolls-Royce Deutschland lowspeed compressor stator cascade 14,22,25 characterized with low aspect ratio and overcritical turning is investigated. The blade cascade is depicted in Figure 1(a).…”
Section: Computational Procedures Cascade and Synthetic Jet Actuatormentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, a Rolls-Royce Deutschland lowspeed compressor stator cascade 14,22,25 characterized with low aspect ratio and overcritical turning is investigated. The blade cascade is depicted in Figure 1(a).…”
Section: Computational Procedures Cascade and Synthetic Jet Actuatormentioning
confidence: 99%
“…Apart from steady control techniques presented above, unsteady active flow control techniques could improve flow behaviors in the blade passage remarkably with relatively small local energy addition, which would reduce the required jet flow and improve the control efficiency. [13][14][15][16] As an unsteady active flow control technique based on the motion of vortex, synthetic jets possess unique superiority of compact structure, no pipe requirement and easily controlled actuation parameters, which have been widely used in the fields of flow separation control, heat and mass transfer enhancement and noise suppression, etc. 17 The synthetic jet is essentially a zero-net-mass-flux jet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glezer et al [2] conducted the experiment on synthetic jet technology and found that the synthetic jet has great potential for controlling flow separation. Gmelin et al [5] used numerical and experimental methods to conduct the synthetic jet control on a high-loaded low-speed compressor cascade. The numerical simulation and experimental results are in a good agreement.…”
Section: Introductionmentioning
confidence: 99%
“…Unsteady excitation showed a great potential in improving cascade performances under appropriate excitation frequencies, amplitudes, and locations, and also there existed a most effective excitation frequency, which was exactly equal to the characteristic frequency of vortex shedding. 12,13 The experimental and numerical investigations were employed by Gmelin et al 14 in a high-loaded compressor cascade with steady jets, pulsed jets, and synthetic jets. For three kinds of flow control configurations, the control effects of flow separations were more distinct when their best excitation locations were selected.…”
Section: Introductionmentioning
confidence: 99%